Management of acute heart failure in the intensive care unit - Chidhambharam Lakshmanan; Priyavarthini Venkatachalapathy; Parvathy S. Menon; R. Vikram Rajkumar (Journal of Pediatric Critical Care)
Pediatric heart failure (PHF) is a heterogeneous syndrome arising from varied etiologies including congenital heart disease, genetic, infective, inflammatory, and metabolic disorders. The aim of acute heart failure (HF) management is to achieve euvolemic state with adequate cardiac output and peripheral perfusion. Management is guided by the severity of HF and assessment of volume and perfusion status of the patient. This includes pharmacological interventions such as diuretics, inotropes, vasodilators, timely, and appropriate use of invasive and noninvasive ventilation. Early achievement of these goals will help avoid deleterious effects of inotropes on already failing myocardium and a smooth transition to oral HF medicines. In children who are not stabilized with medical management, early initiation of mechanical circulatory support (MCS) including extracorporeal membrane oxygenation and ventricular assist devices, before onset of significant organ dysfunction should be considered. MCS serves as a bridge to recovery or transplantation or decision-making or occasionally as destination therapy.